Proses Keagenan dalam Perpanjangan Sertifikat Safe Manning di Kantor Syahbandar Kelas IV oleh PT. Bahtera Adhiguna Cabang Pangkalan Susu: Penelitian - Meriah Kita Deliani; Yoses Sola Gratia Sembiring (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The purpose of this study is to examine the role of shipping agents in the arrival process of the passenger vessel MV Star Voyager at PT. Samoda Raya Bahari. Shipping agents play a crucial role as official representatives of ship owners by acting as intermediaries between the vessel and relevant port authorities, including the port authority, customs, immigration, quarantine services, and port service providers.The data collection methods employed in this study include field research through direct observation and communication with related stakeholders, as well as library research by reviewing books and academic journals relevant to the research topic. The results indicate that the role of the shipping agent in handling the arrival of MV Star Voyager at PT. Samoda Raya Bahari has not yet been optimal. This condition is primarily caused by inefficiencies in arrival time resulting from expired ship documents, which delay the clearance-in process. To optimize the handling of vessel arrivals, PT. Samoda Raya Bahari has implemented several improvement strategies, including early verification of clearance-in documents, increasing the number of employees, providing agency training and education, and enhancing office facilities and infrastructure.